2007
DOI: 10.1002/cbf.1437
|View full text |Cite
|
Sign up to set email alerts
|

Role of CYP2C9 and CYP2C19 polymorphisms in patients with atherosclerosis

Abstract: The arachidonic acid metabolizing CYP enzymes with prominent roles in vascular regulation are epoxygenases of the two gene family which generate epoxyeicosatrienoic acids. Carriers of CYP2C9 mutant alleles exhibit a diminished CYP2C9 metabolic capacity leading to decreased endothelium-derived hyperpolarizing factors (EDHF) synthesis and an increased risk for atherosclerosis. We investigated whether the polymorphisms of CYP2C9/19 are related with atherosclerosis. We examined 108 patients having angioraphically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
3
33
0
1
Order By: Relevance
“…P-values derived from likelihood ratio from z-statistics of the Cox regression model. CYP2C9*2 and CYP2C9*3 and risk of atherosclerosis D Kaur-Knudsen et al polymorphisms and ischemic vascular disease, [21][22][23][24] in accordance with this study. Erroneous genotyping could explain a failure to detect a true association, but we consider this highly unlikely in our study as we included positive controls in all genotype reactions, and also because genotypes were confirmed by sequencing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…P-values derived from likelihood ratio from z-statistics of the Cox regression model. CYP2C9*2 and CYP2C9*3 and risk of atherosclerosis D Kaur-Knudsen et al polymorphisms and ischemic vascular disease, [21][22][23][24] in accordance with this study. Erroneous genotyping could explain a failure to detect a true association, but we consider this highly unlikely in our study as we included positive controls in all genotype reactions, and also because genotypes were confirmed by sequencing.…”
Section: Discussionsupporting
confidence: 90%
“…8 Our findings contrast some, 19,20 but not all, studies. [21][22][23][24] A Swedish study published in 2003 reported a modest increased risk of MI among women carrying CYP2C9 polymorphisms (172 MI cases/1503 controls). 20 Another case-control study, however, found that CYP2C9 polymorphisms in men were associated with decreased risk for MI (403 MI cases/431 controls), but found no risk association in women.…”
Section: Discussionmentioning
confidence: 99%
“…No association between CYP2C9*2 and CYP2C9*3 polymorphisms and risk of subclinical atherosclerosis, ischemic vascular disease (ischemic heart disease, myocardial infarction, ischemic cerebrovascular disease and ischemic stroke) or cardiovascular death was found in a very large Danish study [61]. Similarly, an association with coronary atherosclerosis, detected by angiography, was found in a small study performed in Turky [62]. In a mixed population from the USA, mostly of Caucasian ethnicity, no association with myocardial infarction and stroke was observed in a haplotype analysis using 8 and 7 tag SNPs for the CYP2C8 and CYP2C9, respectively [63].…”
Section: Cyp2c8 Cyp2c9 Hypertension and Cardiovascular Diseasesmentioning
confidence: 86%
“…The CYP2C19*3 mutant A allele changes the tryptophan codon to the termination codon which results in protein synthesis stopping earlier and consequently a truncated protein with a defective heme-binding region (Ercan et al, 2008). Cytochrome P450 epoxygenases metabolize arachidonic acid to EETs.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C19 is one of the human cytochrome P450 enzymes, and it is abundantly expressed in endothelial and smooth muscle cells (Imig et al, 2000;Ercan et al, 2008). CYP2C19 is the key enzyme of EET synthesis.…”
Section: Introductionmentioning
confidence: 99%